Feeding sunflower meal with pullets and laying hens even at a 30% inclusion rate does not impair the ileal digestibility of most amino acids - Such, Nikoletta; Mezőlaki, Ákos; Tewelde, Kesete Goitom; Pál, László; Horváth, Boglárka; Poór, Judit; Dublecz, Károly (Frontiers in Veterinary Science, 2024)
The use of locally available protein sources in poultry nutrition is challenging for feed manufacturers and farmers. Sunflower meal (SFM) is available in high quantities in several European countries and could be used as a poultry feedstuff at higher inclusion rates. However, its maximum inclusion rate in the diets of different poultry species and age categories is unknown. Pullets and laying hens can probably tolerate higher amounts of SFM, but only limited information is available on these poultry groups. Therefore, a digestibility trial was carried out with 8-week-old layer type pullets and 50-week-old laying hens. Beside a basal diet, SFM was fed at 10, 20 and 30% inclusion rates. Feeding SFM significantly improved the digestibility of essential amino acids (AA) of threonine, valine, lysine, tyrosine, glycine, aspartic acid, and arginine in the pullet diets. No such improvement was found in laying hens. Only the absorption of the two branch-chain AAs, leucin (pullets) and isoleucine (hens), declined due to SFM. The AA digestibility of the SFM itself was also calculated by linear regression. The coefficients were, in all cases, higher in hens than in pullets. Comparing the measured digestibility coefficients of SFM with table values, it can be concluded that high variance exists because of the differences in the methodology and the test animals in the digestibility trials. From the present trial, it can be concluded that SFM can entirely replace extracted soybean meal in pullet and layer diets, without negative effects on the protein digestion of birds.